2004
DOI: 10.1161/01.hyp.0000103696.60047.55
|View full text |Cite
|
Sign up to set email alerts
|

Adrenomedullin Protects Against Myocardial Apoptosis After Ischemia/Reperfusion Through Activation of Akt-GSK Signaling

Abstract: Abstract-Adrenomedullin (AM) is a potent vasoactive peptide and plays an important role in cardiovascular function. In this study, we delivered the AM gene locally into the heart, using a catheter-based technique to investigate the signaling mechanism mediated by AM in protection against cardiomyocyte apoptosis induced by acute ischemia/reperfusion. After adenovirus-mediated gene delivery, highly efficient and specific expression of luciferase, green fluorescent protein, or recombinant human AM was identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 43 publications
2
64
0
Order By: Relevance
“…10 In fact, CGRP and ADM have been reported to be upregulated in plasma and cardiovascular tissues in cardiac ischemic diseases. 16,23,24 They effectively antagonize the deleterious actions of angiotensin II 25,26 and endothelin 26,27 in different cardiovascular diseases, which indicates that IMD might counteract vicious stimuli in a similar way. 10 Although the IMD gene delivery technique has not been applied to ameliorate conditions of cardiac ischemia, Hagiwara et al 28 have fully shown that a delivered human IMD gene not only produced a sustained reduction of blood pressure but also attenuated renal dysfunction in DOCA-salt hypertensive rats by inhibition of oxidative stress and proinflammatory mediator pathways.…”
Section: Discussionmentioning
confidence: 99%
“…10 In fact, CGRP and ADM have been reported to be upregulated in plasma and cardiovascular tissues in cardiac ischemic diseases. 16,23,24 They effectively antagonize the deleterious actions of angiotensin II 25,26 and endothelin 26,27 in different cardiovascular diseases, which indicates that IMD might counteract vicious stimuli in a similar way. 10 Although the IMD gene delivery technique has not been applied to ameliorate conditions of cardiac ischemia, Hagiwara et al 28 have fully shown that a delivered human IMD gene not only produced a sustained reduction of blood pressure but also attenuated renal dysfunction in DOCA-salt hypertensive rats by inhibition of oxidative stress and proinflammatory mediator pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this protection from apoptosis was inhibited by dominant-negative Akt or active GSK-3β mutant and mimicked by pharmacological inhibitors of GSK-3β. 69,[94][95][96][97][98] Transgenic mice that cardio-specifically express dominantnegative GSK-3β showed significantly fewer apoptotic cardiomyocytes after pressure overloading by aortic constriction. 99 These findings indicate that GSK-3β activity determines the fate of cardiomyocytes exposed to apoptosis inducers.…”
Section: Role Of Gsk-3β In Apoptosis Of Cardiomyocytesmentioning
confidence: 99%
“…Although the role of GSK-3β in apoptosis of cardiomyocytes has not been fully clarified, evidence to date supports its significant contribution to apoptosis induced by ischemia/ reperfusion, 69,[94][95][96] hypoxia/re-oxygenation, 97 β-adrenoceptor activation 98 and pressure overload. 99 Apoptosis by these insults was suppressed by overexpression of the adrenomedullin gene 95 or kallikrein gene 96 or treatment with statins, 97 all of which induced phosphorylation of GSK-3β.…”
Section: Role Of Gsk-3β In Apoptosis Of Cardiomyocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In addition, age-matched male C57BL/6 (wild type, WT) mice were purchased from Charles River (Wilmington, MA, USA). Studies were performed in: (i) sham-operated (normal) mice and (ii) WT or a-CGRP KO mice that (immediately after BDL) were treated with saline or the CGRP receptor antagonist, CGRP (0.55 mg/kg body weight/day by IP-implanted Alzet s minipumps) 26 for 3 or 7 days. BDL was performed as described.…”
Section: Animal Modelsmentioning
confidence: 99%